2016
DOI: 10.1016/j.cell.2015.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Raphe Dopamine Neurons Represent the Experience of Social Isolation

Abstract: SummaryThe motivation to seek social contact may arise from either positive or negative emotional states, as social interaction can be rewarding and social isolation can be aversive. While ventral tegmental area (VTA) dopamine (DA) neurons may mediate social reward, a cellular substrate for the negative affective state of loneliness has remained elusive. Here, we identify a functional role for DA neurons in the dorsal raphe nucleus (DRN), in which we observe synaptic changes following acute social isolation. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
273
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(292 citation statements)
references
References 73 publications
15
273
2
2
Order By: Relevance
“…Further testing employing these individual cellular resolution approaches or alternatively, fiber photometry directed toward explicit terminal fields (Chen et al, 2015), given the one-to-one ARC AgRP neural architecture (Betley et al, 2013), would begin to elucidate these questions. Importantly, projection-defined ARC AgRP neurons target a number of downstream areas that fail to elicit acute feeding behavior giving rise to the possibility that these efferents modulate surrogate behaviors such as mating and territorial aggression (Falkner and Lin, 2014; Matthews et al, 2016; Padilla et al, 2016; Yang and Shah, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Further testing employing these individual cellular resolution approaches or alternatively, fiber photometry directed toward explicit terminal fields (Chen et al, 2015), given the one-to-one ARC AgRP neural architecture (Betley et al, 2013), would begin to elucidate these questions. Importantly, projection-defined ARC AgRP neurons target a number of downstream areas that fail to elicit acute feeding behavior giving rise to the possibility that these efferents modulate surrogate behaviors such as mating and territorial aggression (Falkner and Lin, 2014; Matthews et al, 2016; Padilla et al, 2016; Yang and Shah, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Sources of dopaminergic innervation of the Drd/Pet1 subtypes may include the rostral DR in addition to the SNc and midbrain VTA. While the midbrain VTA dopaminergic neurons have been shown to directly impact aggressive behaviors (Yu et al, 2014), the rostral DR dopaminergic neurons have recently been shown to influence the subjective experience of social isolation (Matthews et al, 2016). It remains to be definitively demonstrated, however, whether dopamine-mediated regulation of serotonergic neurons influences serotonin-mediated modulation of aggressive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Because serotonergic DR neurons influence postpartum physiology and behavior (Barofsky et al, 1983), their loss would be particularly impactful for the mothers. Additionally, the rostral DR is densely populated by dopaminergic neurons that encode the negative valence of social isolation and then drive the motivation to socially interact (Matthews et al, 2016). Elevated loss of these dopaminergic neurons during late lactation may facilitate weaning of the pups, which could otherwise produce aversive social isolation for the dams.…”
Section: Conclusion and Discussionmentioning
confidence: 99%